John Bundle / Muhamad Syafizan Syafiq... [et al.] - Syafiq, Muhamad Syafizan; Usali, Muhammad Farizan; Ibrahim, Muhammad Ridzuan; Wan Mazlan, Wan Muhammad Hafiz (2021)
We are establishing a store called “John Bundle” intend to start our business. We are selling variety of apparel products. They are categorized as clothing, caps, shoes, belts and bags. Each category we sort by grade. Most category have A and B grade but there is a C grade product. Those products also come in varies material, so our costumer can choose to their personal choice. The price that we charge depends on the category and type of material. Material like leather will cost a lot more than cotton. We do a price survey on different store around our expected location and analyze it. Then, we do our pricing according to those survey, other factors also been considered when we do pricing. All that, so we can compete with our competitors and take advantage of their weakness. We believe that our products will capture people hearts and penetrate the market share soon and later increase our share. This business venture has been established on 22 December 2017 and we only operating with all four of us as a start. We believe that all four of us can cover all the work for now as we know each other capability. Maybe we will need employees to fill positions like salesman, driver, accountant assistant and cashier. We will be operating at PT 536, Jalan Jambatan Sultan Yahya Petra, Seksyen 17, Kampung Sireh 15050 Kota Bharu, Kelantan. Our competitors are AEON mall, Tesco supermarket and Segark Fashion which located near our store. Their strengths are highly-known for their high- quality products and experienced staff, also they have been established for a long time. The counterpart, their weaknesses are quite expensive products, have limited space and low variety of products. We intend to introduce our product to our costumer by first, product strategy which are product brand, quality and labelling. Second, price strategy is based on cost and competition. There are factors that affect our pricing such as economic condition, government regulation and consumer group. Third, promotion strategy basically has three ways which are by social media (Facebook and Instagram), printed media (business card and banners).